Work Will Not Save Us: An Asian American Crip Manifesto - Mel Y. Chen; Mimi Khúc; Jina B. Kim (Disability Studies Quarterly, 2023)
Drawing together disability justice, Asian American studies, and feminist/ queer-of-color labor analysis, this collaboratively authored essay forwards an anti-work manifesto shaped by our lived experiences as sick, disabled and queer Asian American scholars laboring in the academic-industrial complex. This essay offers a two-part intervention: first, it aims to expand nascent conversations on disability politics and its relationship to racial capitalism, and second, it puts forth a critique of the Asian American emphasis on achievement as an instrument of belonging and potential inoculation against racialized violence. It also unfolds in two parts: first, a section on why we refuse work, and second, a section on how to perform this refusal.